ANTIMICROBIAL AND PHYTOCHEMICAL INVESTIGATION OF CALOTOROPIS PROCERA FLOWERS EXTRACTS - ALTAYEB, SARA HUSSEIN; KHALID, ASAAD (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Objective: The present study was planned to screen extracts of different polarities of the flowers of Calotropis procera for the detection of different secondary metabolites, estimate the antibacterial activity of the prepared extracts, and study the active extracts by different chromatographic and spectroscopic methods. Methods: The diethyl ether, methanol, and water extracts were phytochemically screened. Petroleum ether, chloroform, and methanol extracts were also tested against two Gram-positive bacteria, namely Bacillus subtilis and Staphylococcus aureus, and two Gram-negative bacteria, namely E. coli and Pseudomonas aeruginosa with diffusion method. The methanolic extract was further investigated by column chromatography (CC) and preparative thin-layer chromatography (PTLC). Three pure compounds have been isolated and investigated by IR-spectroscopy. Results: Phytochemical screen showed the presence of various secondary metabolites such as flavonoids, alkaloids, steroids, cardiac glycosides, reducing sugars, and saponins. The antibacterial assay revealed that the methanolic extract was the most active against the tested bacteria, especially against Pseudomonas aeruginosa with the high zone of inhibition (23 mm) at 100 mg/ml, and E. coli (22 mm) at 100 mg/ml, followed by chloroform extract, while the petroleum ether extract was insignificantly active. Column Chromatography analysis of the methanolic extract separated fifteen fractions. The PTLC of fraction No.14 enabled the isolation of three pure compounds (A, B, and C). The IR-spectroscopy analysis of the three isolated compounds exhibited that they could referred to the alkaloids or cardiac glycosides. Conclusion: The methanolic extract showed significant activity against tested bacteria, especially E. coli and Pseudomonas aeruginosa. The result also indicates the presence of secondary metabolites in C. procera extracts. Subsequently the therapeutic efficacy compounds isolated and purified from C. procera could be used as an important source against bacterial ailments in humans and plants.